Accommodation Amplitude Before and After Laser-assisted in Situ Keratomileusis (LASIK) in Myopic Patients - Bonita Asyigah; Ani Ismail (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2020)
Introduction: Laser-assisted in situ keratomileusis (LASIK) is the most common refractive surgery to treat myopia. One of the most common complain after this procedure is blurry near-vision. This study was aimed to evaluate the role of accommodation amplitude (AA) in myopic patients before and after LASIK and its effect to blurry near-vision in myopic patients after LASIK. Methods: Patients with myopia who underwent LASIK procedure in Sriwijaya Eye Center Hospital from January to February 2018 studied prospectively. AA was assessed before and after LASIK with 1 day, 1 week and 1 month. Myopia degree, intraocular pressure (IOP), age, gender, ablation and corneal profile were also assessed. Results: A total 52 eyes from 32 patients were included. Visual acuity (VA) of all sample were significantly improve in 1 day after LASIK (p 0,001). Mean AA in myopic patients before LASIK 9,25 D and AA 1 day after LASIK were all significantly decrease into 9,00D (p 0,012) which can cause in blurry near- vision after LASIK. In 1 month followed- up, mean AA is significantly improved into 11,00 D (p 0,000) with no complain. Other factor that affect the changing AA were corneal cell density (CD), IOP and AA before LASIK. Conclusions: There is significant AA difference in myopic patients before and after LASIK. Blurry near-vision after LASIK is caused by AA adaptation mechanism after LASIK.